Prevalence and prognosis of subjects with Brugada-type ECG pattern in a young and middle-aged Finnish population - Junttila, M J; Raatikainen, M J P; Karjalainen, J; Kauma, H; Kesäniemi, Y A; Huikuri, H V (European heart journal, 2004)
The purpose of this study was (1) to determine the prevalence of Brugada syndrome ECG abnormalities ("Brugada sign") in two Finnish populations and (2) to evaluate the natural course of subjects with the "Brugada sign". The study population consisted of 2479 healthy male Air Force applicants (age 18-30 years), and 542 healthy middle-aged subjects (age 40-60 years). All subjects underwent a thorough physical examination and 12-lead ECG in 1980-1990 (first population) and in 1991-1992 (second population). The ECG criteria suggested by the European Society of Cardiology were used to identify subjects with the "Brugada sign". Fifteen (0.61%) subjects in the first population and three subjects in the second population (0.55%) fulfilled the ECG criteria for type 2 or 3 Brugada syndrome, i.e., they had J-point elevation and a saddleback-type ST-segment configuration in the right precordial leads. Type 1 Brugada ECG abnormality (coved ST-segment elevation) was not seen in any subject. No mortality or life-threatening ventricular arrhythmias occurred in either study population during follow-up (19+/-2 years and 11+/-1 years, respectively). The benign natural course of the patients with the "Brugada sign" suggests that in asymptomatic subjects without a family history of sudden cardiac death, type 2 or 3 Brugada ECG pattern is a normal variant rather than a specific predictor of life-threatening ventricular arrhythmias.